Aspects Of The Quality Of Financial Reports : THE QUALITY OF FINANCIAL REPORTS - Anwar Anwar; Syiar Rinaldy; Asbi Amin (Jurnal Penelitian Ekonomi dan Akuntansi (JPENSI), 2023)
This research is important to study because it looks at the phenomena and results of previous research, so this study aims to examine the effect of applying PSAK 101, the internal control system and the performance of internal auditors on the quality of financial reports. The population in this study is a limited population, namely the internal auditors from 13 Indonesian Sharia Bank Branch Offices in Makassar city as many as 39 auditors. The sample technique is the saturated sample technique. Data were analyzed by multiple linear regression analysis. The results of the study found that the application of PSAK 101, the internal control system and the performance of the internal auditors have a significant effect on the quality of financial reports.